Event tourism: concepts, types, classification (Journal of Geography and Environmental Management, 2018)
The article is devoted to event tourism as a promising area of tourist activity, which gained wide popularity in the world and is at the stage of becoming in Kazakhstan. For today it is possible to state precisely that event tourism differs among other varieties of tourism and is unique. It is worth noting also the fact that for a short time this type of tourism has gained unprecedented popularity in Kazakhstan, due to the holding of large-scale events like the Winter Universiade -2017 in Almaty, EXPO-2017 in Astana. The aim of the research is to analyze the theoretical aspects of event tourism and to make a classification of event tourism. In the article the works of domestic and foreign scientists devoted to the problems of event tourism are analyzed. The conceptual apparatus, the structure of event tourism is considered. The research method is based on a comparative analytical method consisting in the identification, analysis and evaluation of the existing approaches in the classification of event tourism. As a result of the study, a classification of event tourism was compiled. Six basic criteria for the evaluation of event tourism have been singled out, taking into account the classification of events of event tourism (by the scale of the event, by purpose, by professional directions, by the composition of participants, by the type of organizers). The practical significance of the research is determined by the fact that the scientific problems raised are directly related to the solution of urgent problems and can be used as a basis for further research of event tourism.